Acute Behavior of Oxygen Consumption, Lactate Concentrations, and Energy Expenditure During Resistance Training: Comparisons Among Three Intensities - João, Gustavo A.; Almeida, Gustavo P. L.; Tavares, Lucas D.; Kalva-Filho, Carlos Augusto; Carvas Junior, Nelson; Pontes, Francisco L.; Baker, Julien S.; Bocalini, Danilo S.; Figueira, Aylton J. (Frontiers in Sports and Active Living, 2021)
The present study aimed to compare the oxygen consumption, lactate concentrations, and energy expenditure using three different intensities during the resistance training sessions. METHODS: Fifteen males (22.9 ± 2.61 years) experienced in resistance training underwent three sessions composed of eight exercises (chest press, pec deck, squat, lat pull-down, biceps curl, triceps extension, hamstring curl, and crunch machine), which were applied in the same order. The weight lifted differed among the sessions (high-session: six sets of five repetitions at 90% of 1-RM; intermediary-session: three sets of ten repetitions at 75% of 1-RM; and low-session: two sets of fifteen repetitions at 60% of 1-RM). The oxygen consumption (V̇O2) – during and after (EPOC) the session – blood lactate, and energy expenditure (i.e., the sum of aerobic and anaerobic contributions, respectively) were assessed. RESULTS: the V̇O2 significant decreased in the function of the weight lifting (F(2.28) = 17.02; p < 0.01; ηG2 = 0.32). However, the aerobic contributions significantly increase in function of the weight lifting (F(2.28) = 79.18; p < 0.01; ηG2 = 0.75). The anaerobic contributions were not different among the sessions (p > 0.05; ηG2 < 0.01). Thus, the total energy expenditure during the session (kcal) significantly increased in function of the weight lifting (F(2.28) = 86.68 p < 0.01; ηG2 = 0.75). The energy expenditure expressed in time unit (kcal·min-1) was higher in low-session session than in high-session (F(2.28) = 6.20; p < 0.01; ηG2 = 0.15). CONCLUSION: The weight lifted during resistance training induced different physiological responses, which induced higher energy expenditure per unit of time during low-session.